PENERAPAN TARGET COSTING DALAM UPAYA PENGURANGAN BIAYA PRODUKSI UNTUK MENGOPTIMALKAN LABA KOTOR (Studi Pada UD. Tahu Suhandi Kotacane) - Hutagalung, Daniel; Silalahi, Evelin Roma Riauli; Sihotang, Helena (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The purpose of this study was to determine and analyze the application of target costing in an effort to reduce production costs to optimize gross profit at UD Tahu Suhandi Kotacane. The population in this study is the entire income statement of UD Tahu Suhandi Kotacane from 1976 to 2021. The sample is part of the population, where the sample used is the report on production costs and the income statement in producing tofu during 2019 to 2021. Data collection techniques in this study were carried out with documentation and observation techniques. The analytical technique used in this research is descriptive data analysis technique which aims to describe the object of the research by collecting production cost reports and income statements. Based on the results of research conducted, it can be seen that the difference between the calculation of the traditional method of production costs and the target costing method is Rp. 31,300,000 (labor costs Rp. 25,040,000 + factory overhead costs Rp. 6.260,000). By using the target costing method, UD Tahu Suhandi got a gross profit in 2019 of Rp.225,628,300, where the gross profit is expected to increase by 10% from 2018 of Rp.213,463,730. In 2020 the gross profit obtained was Rp.229,828,900, where the gross profit is expected to increase by 10% from 2019 which was Rp.217,961,730. Meanwhile, in 2021 the gross profit obtained is Rp. 237,967,100, where the gross profit is expected to increase by 10% from 2020 of Rp. 226,519,990. Thus, the application of target costing is very useful to be applied to UD Tahu Suhandi, not only reducing production costs but realizing the desired profit which was previously only 10% or even more than expected. Keywords: Target costing, Production Costs, Gross Profit